The influence of therapeutic riding on the balance of children and adolescents with autistic spectrum disorder: an integrative literature review (Research, Society and Development, 2022)
Autism Spectrum Disorder (ASD) is defined as a neurodevelopmental disorder in which the first symptoms appear in early childhood. In order to reduce the complications caused by the disease, children with ASD undergo physiotherapy sessions, and among the resources used, horseback riding has stood out as a complementary resource.  This study aimed to systematize the scientific evidence about this resource, in order to provide a better understanding of the therapy, favoring subsidies for future research. This is an integrative literature review with a descriptive and qualitative approach, carried out through bibliographic research in SciELO, PubMed and LILACS databases. 5 scientific articles were selected, based on the descriptors "autistic spectrum disorder", "assisted horseback riding" and "postural balance". All evidence pointed to consistent conclusions about the benefits of the practice of equine therapy on the health of children and adolescents with ASD. It was possible to conclude that the regular practice of equine therapy is appropriate and indicated as a therapeutic plan for children and adolescents with ASD; however, further studies on the theme are necessary, since there is a lack of bibliographic reference on the benefits of equine therapy on the balance of children and adolescents with ASD.